Information retrieval algorithms and heuristics - Grossman, David A. 1965-; Frieder, Ophir (Dordrecht, The Netherlands Springer, 2004)
Examples are used throughout to illustrate the algorithms.The authors explain how a query is ranked against a document collection using either a single or a combination of retrieval strategies, and how an assortment of utilities are integrated into the query processing scheme to improve these rankings.
Previous ed.: Boston ; London : Kluwer, c1998.
Includes bibliographical references and index.
E2-557G donated by Mr. Johnson Apacible.
Keywords: Information storage and retrieval systems